Development of The Gotang Game Model Towards Students’ Active Participation of Class V Physical Education Learning - Moh. Alif Arya Ayomi; Agus Pujianto (Universitas Negeri Semarang, 2026)
This study aims to develop the GOTANG game model as an alternative for physical education learning to increase the active participation of fifth-grade elementary school students in Semarang City. This research is motivated by students' low in-terest in traditional games and limited facilities and infrastructure in learning large ball games, especially handball. This study used the Research and Develop-ment (R&D) method with the ADDIE model (analysis, design, development, imple-mentation, and evaluation). Data collection was conducted through observation, interviews, and questionnaires. Data analysis used quantitative and qualitative descriptive analysis using the Guttman scale. A small-scale trial was conducted on 15 students from SDN Pakintelan 2, while a large-scale trial was conducted on 45 students from SDN Pakintelan 2 and Pakintelan 3. Product validation involved game experts and physical education experts. The results of the study are as fol-lows: (1) The validation data according to experts is 97% in the sufficient category. (2) The results of small-scale trials were 92% with Good category, and (3) The re-sults of large-scale trials were 90% in the Good category. The product resulting from this development is a model of the Gobak Sodor Bala Tangan (GOTANG) game that can be assembled and disassembled. The Gotang game has been de-clared suitable for use as a learning model for physical education materials in elementary schools.